Water as the Earth’s Buffer and Immune System - Vladyslav V. Goncharuk (Journal of Chemistry)
A comprehensive review on water as a buffer of the planet and its immune system is presented. The relationship between the quality of drinking water, the level of development of human intelligence, and its health is highlighted. The problems of obtaining cytogenetically and physiologically safe high-quality drinking water are discussed along with the problems of its decontamination. The solutions to maintain stable development of aquatic ecosystems are proposed. It is shown that tap water is the habitat of multiresistant genetically-mutated microorganisms.